A mini-review on anaerobic digestion of Indonesian macroalgae biomass: present scenario and future scope - Elviliana Elviliana; Sri Suhartini; Nur Hidayat; Hans Oechsner (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Macroalgae as the marine renewable biomass has great potential for production of bioenergy and bioproduct with integrated biorefinery concept. However, high lignin content may hinder the valorization. Same conditions applied for the macroalgae in Indonesia which has the great opportunity to explore more in the bioenergy field. This study aimed to investigate potential application of macroalgae as substrates for bioenergy production, specifically with anaerobic digestion (AD) technology. Anaerobic digestion as the one of the ways to transform macroalgae into biogas. This review analyses the latest study’s results from the view of composition, degradation, and the biorefining pathways. The biomass is constructed from lignocellulose compounds and have thick cell wall that be the main drawbacks for the biochemical conversion technology. Various enhancement pathways have been studied i.e., pretreatment methods to enhance the accessibility for microorganisms, reduce the outer cell wall thickness, and co-digestion with addition of other substrates to balancing the nutrition and providing the stable condition for AD system. In term to have more feasibility from economic view, the strategy is put in the biorefinery concept to have more valuable-added products. The decrement of energy input, higher of energy output and yield of outcome along with some products being produced are expected to gain from the proposed ways. Those information will provide new research directions and solutions for converting Indonesia marine macroalgae using AD technology.